ANALISIS PROFIL KONSUMEN UNTUK PEMBUATAN APLIKASI INDEKOS DENGAN PENDEKATAN DESAIN PROPOSISI NILAI - Nugroho Wisnu Murti; Kristina Sisilia (Fakultas Ekonomi dan Bisnis, 2019)
They are seeing the development of internet users in Indonesia which is growing rapidly. This is the basis for the emergence of applications that can facilitate the community in doing their work. One of them is doing work in terms of finding a homestay, especially in the student segment. The phenomenon found, the information offered is incomplete and the absence of services to help move goods. This study aims to determine the consumer profile which includes perceptions and expectations for the homestay application customer segment, namely students, so that it can be a reference for creating value propositions that are relevant for homestay applications. The study uses a qualitative approach that is descriptive. Data collection techniques used include interviews, observation, and documentation. In this study, the design of a consumer profile consists of three parts, namely customer jobs, customer science, and customer gains in the Value Proposition Design taken from Alexander Osterwalder and Yves Pigneur. In this study, generated perceptions and expectations of consumers of boarding room applications, among others, requires complete information, a lot of boarding references, there are features of ratting, booking, and chat forums, as well as there are goods transport services.